A narrative exploration of women’s experiences of intimate partner violence in the home during the COVID-19 lockdown in the Westlake community, South Africa. - Bester, Anita (Stellenbosch : Stellenbosch University, 2025)
Thesis (MA)--Stellenbosch University, 2024.